The influence of fertilization and tillage method on the formation root system capacity and grain production of spring barley - Kupecsek, Andrej; Molnárová, Juliana (Acta Agraria Debreceniensis, 2011)
To evaluate the interaction of year x variety, year x tillage method and year x fertilization on the grain yield and root system capacity (RSC) of spring barley, we ran polyfactorial field trials in agroecological conditions of a warm corn production area in Slovakia, at  Malanta, in 2009 and 2010. The RSC measurements were done using LCR - meter at a frequency of 1 kHz and they took place in four growth stages: at leaf development in the stage of four leaves (RSC1), in full tillering (RSC2), in the stage heading (RSC 3) and at the stage of ripening (RSC4). The values of grain yield, RSC1, RSC2, RSC3, RSC4 reached in 2009 comparison to 2010 were significantly lower. The highest yield in 2009 was reached by variety Marthe (4.49 t.ha-1) and by variety Bojos (7.19 t ha-1) in 2010. The highest values of RSC in observed growth stages were achieved by variety Bojos in 2009, and in 2010 also besides RSC1. Within both years, difference in yields between tillage methods was not observed. The values of RSC in growth stage of 4 leaves and tillering was higher at conventional tillage, butthe values of RSC3 and RSC4 were higher with minimized tillage. The highest grain yield and values of RSC in every growth stage were achieved on the fertilization variant “c“ in 2009 and on the fertilization variant “b“ in 2010. The correlation relationships between grain yield and RSC were significant and positive in every growth stage. The strongest relationship was found among grain yield and RSC (r=0.6047).